English Proficiency of Lecturers at a Private University in Indonesia: TOEFL and CEFR Standards - Ade Kristianus Kaloeti (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
In the globalization era, it is crucial for lecturers in STIKES Telogorejo Semarang to possess good English proficiency. The proficiency in English can be determined by the score achieved in TOEFL (Test of English as Foreign Language), which is classified based on the standard of CEFR (Common European Framework of Reference for Language). This study aims to identify the English proficiency of lecturers in STIKES Telogorejo Semarang and to determine the appropriate training model to enhance their English proficiency. The data for this article was collected through testing, which was conducted once for the lecturers in STIKES Telogorejo Semarang. The scores were then analyzed using descriptive quantitative methods. The analysis revealed that the level of proficiency in English for lecturers in undergraduate Nursing is A2 Elementary with an average score of 410, for lecturers in undergraduate Midwifery is A2 Elementary with an average score of 394, for lecturers in undergraduate Pharmacy is A2 Elementary with an average score of 439, for lecturers in undergraduate Physiotherapy is A2 Elementary with an average score of 374, and for lecturers in diploma Nursing is A2 Elementary with an average score of 369. Based on the analysis, the suitable training model for lecturers in STIKES Telogorejo Semarang includes listening skills, structure skills, and reading comprehension skills at the Elementary level.